Modeling of Nitrate Leaching during the Fall–Winter Season in Artificially Drained Soils - Alaa El-Sadek (The Scientific World Journal)
The nitrogen processes that occur within the soil play a major role in determining the nitrate leaching to shallow groundwater. In this study, the transport and fate of nitrate within the soil profile were analyzed by comparing field data with the simulation results of a mathematical model. The objective was to study the transport and fate of nitrate within the soil profile and nitrate leaching to shallow groundwater for the fall-winter season, by applying the methodology in Elverdinge experiment, situated in the sandy loam region in Belgium, from October 1, 2000 to March 31, 2001. The analysis by comparing field data with the simulation results of DRAINMOD-N model is given. The research indicated that the DRAINMOD-N model can, after calibration and validation, be used as a useful fertilizer management tool in predicting the nitrate transport and transformation in the soil profile and the nitrate leaching to shallow groundwater and surface waters. The model can also be used as an environmental control when the environmental objective has a greater importance than profits in the agriculture field.